Delayed Presentation of a Congenital Cholesteatoma in a 64-year-old Man: Case Report and Review of the Literature - Davidoss, Nishant; Ha, Jennifer; Banga, Rupan; Rajan, Gunesh (Journal of Neurological Surgery Reports, 2014)
Introduction Congenital cholesteatomas of the temporal bone are epidermoid cysts of embryologic origin that result in progressive desquamation and trapping of squamous epithelium behind an intact tympanic membrane. They are benign, slowly progressive lesions that can be found in various areas of the temporal bone. We report a case of a patient with a massive cholesteatoma first detected at the age of 64 years, causing significant destruction of the mastoid and petrous temporal bones, and adjacent occipital bone.Methods We reviewed the literature and a case report of a patient seen in our institution recently. The Medline database was used to search multiple terms including “congenital” and “cholesteatoma.”Results The patient's congenital cholesteatoma was detected incidentally on a computed tomography scan when the patient's only symptoms were unilateral conductive hearing loss with a family history of hearing loss. It was subsequently successfully operated on with minimal postoperative complications.Conclusions Congenital cholesteatomas of mastoid origin can often exist for many years in a subclinical state and develop into a massive size before causing symptoms. A high index of suspicion is necessary to detect congenital cholesteatomas in patients with unilateral conductive hearing loss who are otherwise asymptomatic and have a normal tympanic membrane.
Keywords: cholesteatoma; congenital; mastoid; massive; large; incidental; hearing loss; management; review